Types of momentum defect diffusion at the begining of the wake and wake establishment zone for the coupled wake and comparison with the isolated wake - Bich Ngoc, Hoang Thi (Vietnam Journal of Mechanics, 1998)
The article [10] has presented the necessity of the classification into two types: Isolated wakes and coupled wakes. In this report, different types of momentum defect diffusion at the beginning of wake are analyzed for the two types of coupled wake and isolated wake. According to ·numerical results obtained, we analyses the existence - long or short - of the wake establishment zone before the wake established zone, and this zone is very different between isolated wake and coupled wake.